Efek Hirupan Benzene (C6H6) Pada Sel Darah Merah Dan Sel Darah Putih Tikus Putih Jantan (Rattus norvegicus) Strain Wistar - Setiawan, Indra; Margowati, Wahyu Estu Septyah; Andari, Desy; Churochman, Miftha (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
In industry, "benzene" is frequently employed as a basic or compound substance. Exposure to "benzene" has hematotoxic effects on blood cell values, such as pancytopenia. In cases of cytopenia that cannot be explained, a blood smear evaluation is usually employed as a confirmation test and extra diagnostic help. The purpose of this study was to see how benzene inhalation affected blood smear examination in white male rats (Rattus novergicus) of the Wistar strain. True experimental design with simply a post-test control group. A total of 20 rats were separated into four groups. The non-benzene inhalation exposure group (K-) served as the negative control. The treatment groups ("P1, P2, P3") were given benzene inhalation at concentrations of 1, 10, and 100 parts per million, respectively. The exposure lasted 28 days, 8 hours per day, 5 days per week. The results were achieved by counting rat blood cells and examining their morphology under a microscope, after which an average number was calculated. Research and Discussion According to the ANOVA and Kruskal-Wallis test, the number of neutrophils and monocytes increased dramatically, whereas lymphocytes declined. Each group had a varied number of eosinophils, although the difference was not statistically significant. In the group exposed to 100 ppm benzene, the "Bonferoni and Mann-Whitney" post hoc test revealed a significant rise in the number of neutrophil segments and a decrease in the number of lymphocytes "(p0.05)". In the group exposed to 10 ppm benzene, there was a substantial rise in monocytes (p 0,05). The morphology of erythrocytes, leukocytes, and platelets yielded no aberrant results. Benzene inhalation exposure significantly affects the number of neutrophils segments, lymphocytes and monocytes, but has no effect on the number of other types of leukocytes. No abnormal morphology was found in erythrocyte, leukocyte, and platelets.Â